Firm value and cross-listings: The impact of stock market prestige - Nicola Cetorelli; Stavros Peristiani (Federal Reserve Bank of New York, 2010)
This study investigates the valuation impact of a firm's decision to cross-list on a more (or less) prestigious stock exchange relative to its own domestic market. We use network analysis to derive broad market-based measures of prestige for forty-five country or regional stock exchange destinations between 1990 and 2006. We find that firms crosslisting in a more prestigious market enjoy significant valuation gains over the five-year period following the listing. We also document a reverse effect for firms cross-listing in less prestigious markets: These firms experience a significant decline in valuation over the five years following the listing. The reputation of the cross-border listing destinations is therefore a useful signal of a firm's value going forward. Our findings are consistent with the view that cross-listing in a prestigious market enhances a firm's visibility, strengthens corporate governance, and lowers informational frictions and capital costs.
Keywords: G15; G20; 330; Cross-listings; network analysis